Moisture-insensitive, self-powered paper-based flexible electronics - Sala de Medeiros, Marina; Chanci, Daniela; Martinez, Ramses V. (Nano energy, 2020)
The fabrication of multifunctional electronic devices on ubiquitous paper substrates is gaining considerable attention due to their low cost, environmental friendliness, light weight, and flexibility. Unfortunately, the development of paper-based electronics is subject to significant challenges, such as rapid degradation with moisture, battery dependence, and limited compatibility with existing mass production technologies. This work describes omniphobic, self-powered paper-based electronics (RF-SPEs), completely wireless paper-based electronic devices insensitive to moisture, liquid stains, and dust. RF-SPEs can be rapidly fabricated through the sequential spray-deposition of alkylated organosilanes, conductive nanoparticles, polytetrafluoroethylene (strong electron affinity), and ethyl cellulose (weak electron affinity) over the surface of cellulose paper. RF-SPEs are lightweight, inexpensive to print (<$0.25 per device), and capable of generating power densities up to 300 μW/cm2. Additionally, RF-SPEs are flexible and exhibit excellent stability upon folding (0.3 mm radius of curvature). The simple printing process and relative low cost of RF-SPEs enable the large-scale production of self-powered paper-based electronics towards the ubiquitous integration of human-machine interfaces. [Display omitted] •All-spray fabrication of waterproof self-powered paper-based electronics (RF-SPEs).•RFSPEs are foldable and insensitive to moisture, liquid stains, and dust.•Triboelectric areas in RF-SPEs enable self-powered Bluetooth wireless communication.•RF-SPEs enable the low-cost manufacturing of reliable human-machine interfaces.